PRELIMINARY STUDY ON THE GROWTH OF CULTURED PEARLS - Alagarswami, K (Indian Journal of Fisheries, 2011)
Preliminary study on the growth rate of cultured pearls at Veppalodai,Tuticorin, $ugj|eitf that the time taken for the production of a pearl of compara'ble size is copsiderably less in the Indian waters than in the temperate areas ofpearl culture.